Synopsis of Key Gynecologic Oncology Trials. - Renz, Malte; Diver, Elisabeth; Growdon, Whitfield; Dorigo, Oliver (Boca Raton : CRC Press, 2020)
This text is a fast and convenient overview of the clinical trials in gynecologic cancer treatment, setting out the evidence base of treatment decisions in uterine, ovarian, cervical and vulval cancers and gestational trophoblastic neoplasia. Residents and fellows will find this book an indispensable reference for revision, while existing practitioners will welcome it as a clarification of the evidence base for treatment options.
Preface Uterine Malignancies Endometrial Carcinoma Studies addressing surgical treatment Lymph node assessment Studies addressing adjuvant therapy Radiation Chemoradiation Chemotherapy Studies addressing treatment of recurrent endometrial carcinoma Hormonal therapy Chemotherapy Targeted therapy Immunotherapy Uterine Carcinosarcoma Studies addressing prognosticators Studies addressing adjuvant treatment Studies addressing treatment of advanced/ recurrent uterine carcinosarcoma Uterine Leiomyosarcoma Studies addressing adjuvant treatment of early stage uterine leiomyosarcoma Studies addressing treatment of advanced uterine leiomyosarcoma References Ovarian Malignancies Epithelial ovarian cancer (EOC) Studies addressing upfront surgery Studies addressing adjuvant therapy Studies addressing neoadjuvant therapy Studies addressing prediction of debulking Studies addressing time point of treatment of recurrence Studies addressing treatment of recurrent ovarian cancer, platinum-sensitive Chemotherapy and targeted therapy Secondary debulking surgery Studies addressing treatment of recurrent ovarian cancer, platinum-resistant Chemotherapy and targeted therapy Immunotherapy Mucinous epithelial ovarian cancer Ovarian Germ Cell Tumors (GCT) Ovarian Sex Cord-Stromal Tumors (SCT) References Cervical Cancer Studies addressing surgical treatment Studies addressing adjuvant therapy Studies addressing primary chemoradiation therapy Studies addressing treatment of recurrent or metastatic cervical cancer Chemotherapy and targeted therapy Immunotherapy References Vulvar Cancer Studies addressing surgical treatment Lymph node assessment Studies addressing chemoradiation of advanced vulvar cancer References Gestational Trophoblastic Neoplasia (GTN) Studies addressing surgical treatment Studies addressing chemotherapy in low-risk GTN Studies addressing (chemo)therapy in high-risk GTN References Glossary
OCLC-licensed vendor bibliographic record.
Keywords: MEDICAL / General; MEDICAL / Gynecology & Obstetrics; MEDICAL / Oncology; Generative organs, Female -- Cancer